Histopathological and Biochemical Assessment of Neuroprotective Effects of Sodium Valproate and Lutein on the Pilocarpine Albino Rat Model of Epilepsy - Aziza Rashed Al-Rafiah; Khlood Mohammed Mehdar (Behavioural Neurology)
Epilepsy is one of the most frequent neurological disorders characterized by an enduring predisposition to generate epileptic seizures. Oxidative stress is believed to directly participate in the pathways of neurodegenerations leading to epilepsy. Approximately, one-third of the epileptic patients who suffer from seizures do not receive effective medical treatment. Sodium valproate (SVP) is a commonly used antiepileptic drug (AED); however, it has toxic effects. Lutein (L), a carotenoid, has potent antioxidant and anti-inflammatory properties. The aim of this study was to determine the neuroprotective effect of sodium valproate (SVP) and lutein (L) in a rat model of pilocarpine- (PLC-) induced epilepsy. To achieve this aim, fifty rats were randomly divided into five groups. Group I: control, group II: received PLC (400 mg/kg intraperitoneally), group III: received PLC + SVP (500 mg/kg orally), group IV: received PLC + SVP + L (100 mg/kg orally), and group V: received (PLC + L). Racine Scale (RC) and latency period to onset seizure were calculated. After eight weeks, the hippocampus rotarod performance and histological investigations were performed. Oxidative stress was investigated in hippocampal homogenates. Results revealed that SVP and L, given alone or in combination, reduced the RC significantly, a significant delay in latency to PLC-kindling onset, and improved rotarod performance of rats compared with the PLC group. Moreover, L was associated with a reduction of oxidative stress in hippocampal homogenate, a significant decrease in serum tumor necrosis factor-alpha (TNF-α) level, and inhibition of cerebral injury and displayed antiepileptic properties in the PLC-induced epileptic rat model. Data obtained from the current research elucidated the prominent neuroprotective, antioxidant, and anti-inflammatory activities of lutein in this model. In conclusion, lutein cotreatment with AEDs is likely to be a promising strategy to improve treatment efficacy in patients suffering from epilepsy.